Evaluasi Implementasi Kurikulum Merdeka Di SMPN 8 Banjarmasin - Kurniawan, Gilang Dwi; Marini, Marini; Azkia, Resyadilla; Maulidia, Rida; Suriansyah, Ahmad; Purwanti, Ratna (Universitas Pahlawan Tuanku Tambusai, 2025)
The Merdeka Curriculum is an educational policy innovation in Indonesia aimed at improving the quality of learning through a more flexible, student-centered, and responsive approach to contemporary needs. This study aims to describe the implementation of the Merdeka Curriculum at SMP Negeri 8 Banjarmasin, which has gradually adopted the curriculum since 2023. The focus of the research includes the strategies of the principal, teacher readiness, implementation of the Pancasila Student Profile Strengthening Project (P5), and the application of differentiated learning. This research employs a qualitative descriptive method, using data collection techniques such as observation, interviews, and documentation. Data analysis was conducted inductively using Miles and Huberman’s interactive model, which includes data collection, data reduction, data display, and conclusion drawing. The findings of this study are expected to provide a real-world picture of the implementation of the Merdeka Curriculum at the school level and serve as a reference for other schools implementing similar reforms.